Forced sexual victimization among youth in custody: do risk factors vary by gender and perpetrator? - Ahlin, Eileen M. (The prison journal, 2020)
There is relatively little literature examining risk factors associated with sexual victimization among youth in custody. The current study explored whether risk of forced sexual victimization among youth in custody differs by gender or perpetrator. Using data from a sample of 8,659 youth who participated in the National Survey of Youth in Custody, multivariate logistic regression models were employed to investigate gender differences in risk factors associated with overall forced sexual victimization and staff-on-inmate and inmate-on-inmate forced sexual victimization. Findings suggest that gender differences are more pronounced when perpetrator type is considered.